Glycemic Index Meals of Anaerobic Shuttle Test in Endurance Badminton Athletes - Brevi Istu Pambudi; Ekha Rifki Fauzi (Jurnal Dunia Gizi, 2019)
Background; athletes is a person often doing physical exercise, one of exercise is badminton. Athletes need good diet to increase endurance and delay muscle fatigue. Diet should get glycemic index this is also to determine athlete endurance of muscle fatigue. Diet of low or high glycemic index can determine the level of muscle fatigue and find the level of endurance. Objectives; this study aims to examine and determine important factor of effect of low and high glycemic index meals in badminton athletes of the level muscle fatigue. Material and Method; this study used experimental method to examine effect of low and high glycemic index meals in badminton athletes. Subject of this study, all of male amount 20 athletes in age 19-25 years old. Subject included in criteria inclusion and also subject should consume low and high glycemic index meals around 1-2 weeks in each attempt. Results; experiment result of this study revealed significant different of consumed low and high glycemic index meals when the athletes consumed high glycemic index meals, blood glucose increased more than low glycemic index meals (p= 0.021), whereas  effect of high glycemic index meals showed significant of muscle fatigue (p=0.009) than low glycemic index meals. The level of lactate after anaerobic shuttle test, found greater in high glycemic index meals (p=0.02), also high glycemic index meals showed significant reduction of glucose level (p=0.000). Conclusion; low and high glycemic index meals can effect in muscle fatigue of athletes, then low glycemic index meals may increase endurance and delay muscle fatigue.